2008
DOI: 10.3382/ps.2008-00129
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Eimeria Field Isolates in the United States: Responses of Nicarbazin-Containing Anticoccidials

Abstract: A series of studies were conducted to assess the drug sensitivity of 26 coccidial field isolates to the anticoccidial effects of nicarbazin (NIC) and narasin + NIC (NAR + NIC). Isolates were collected from typical broiler farms in the United States from 2003 to 2006, propagated once in the absence of anticoccidial medication, and then used to inoculate broilers that were fed nonmedicated rations or those containing NIC 125 ppm or NAR + NIC 80 ppm. Results of these sensitivity trials indicated that 81% of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Lillehoj et al (2007) reported the use of anticoccidial drugs in feed or water and/or vaccines using live strains of Eimeria in intensively reared poultry settings. Due to the emergence of drug-resistant strains of Eimeria in populations of commercial flocks and increasing public concern about drug residues in meat (Williams, 2006;Bafundo et al, 2008), alternative treatments are urgently needed (Dongjean et al, 2011). Medicinal plants and herbs have been used for many years in the treatment of various diseases in animal and man.…”
Section: Introductionmentioning
confidence: 99%
“…Lillehoj et al (2007) reported the use of anticoccidial drugs in feed or water and/or vaccines using live strains of Eimeria in intensively reared poultry settings. Due to the emergence of drug-resistant strains of Eimeria in populations of commercial flocks and increasing public concern about drug residues in meat (Williams, 2006;Bafundo et al, 2008), alternative treatments are urgently needed (Dongjean et al, 2011). Medicinal plants and herbs have been used for many years in the treatment of various diseases in animal and man.…”
Section: Introductionmentioning
confidence: 99%
“…Control of coccidiosis in poultry flocks currently requires strict husbandry, the use of anti‐coccidial drugs and vaccination . However, significant resistance to anti‐coccidial drugs has been reported and current concerns over antimicrobial resistance in the human food chain are leading to reduction in metaphylactic antibiotic usage. Although immunity to Eimeria in chickens is long‐lasting, vaccination against Eimeria requires multiple live‐attenuated species and strains in order to overcome antigenic variation and ensure immune recognition of these .…”
Section: Introductionmentioning
confidence: 99%
“…4,35 Traditional methods of control include effective management of sanitary procedures, strict biosecurity, prophylactic use of either in-feed synthetic drugs (chemicals) or ionophorous antibiotics, use of disease-resistant chicken lines, and boosting immunity. 9,[36][37][38] However, a serious problem that has surfaced with extensive use of drugs is resistance; this problem needs immediate attention. 7,10,39 The protective effects of sulfonamides have been evaluated extensively and used as the first effective anticoccidial agents.…”
Section: Conventional Coccidiosis Control Strategiesmentioning
confidence: 99%
“…44 Recently, it has been observed that a very high percentage of field isolates of E. acervulina and E. maxima and a significantly high percentage of E. tenella obtained locally from 26 broiler farms in 12 states of the US showed either complete or partial resistance to the combination mixture of nicarbazin and narasin that has been used for a long time in the poultry industry. 36 Surmounting social pressures to withdraw the use of drugs has resulted in poultry producers being judicious with the use of drugs and using alternative methods, including vaccination.…”
mentioning
confidence: 99%